Recent advances in field effect transistor biosensor technology for cancer detection: a mini review. (13th December 2021) - Chao, Lemeng; Liang, Ying; Hu, Xiao; Shi, Huanhuan; Xia, Ting; Zhang, Hong; Xia, Huiling
Abstract: Cancer is an incurable disease, and the treatment process is extremely painful. Early detection may ease the treatment process and prevent cancer from spreading beyond the primary disease area. However, conventional screening tests have long detection times and lack the required sensitivity for early detection. Consequently, traditional cancer biosensors, including amplification refractory mutation system, digital polymerase chain reaction, next generation sequencing, western blot, electrochemical, and mechanical biosensors, have been studied in recent years. Specifically, field effect transistor (FET) biosensors, are attractive pocketable devices with short detection time capabilities. Because FET biosensors have outstanding electrical and mechanical properties, FET biosensors have been studied for their efficacy in the early detection of cancer. Traditional detection methods of cancer biomarkers include the use of FET biosensors for the detection of cancer biomarkers, especially gene, antigen, and protein characteristics. This review presents the latest strategies in FET applications in cancer biosensing and compares their advantages and disadvantages regarding sensing principle, configuration, and performance. Especially, FET biosensors for the detection of cancer biomarkers, which include antibodies, nucleic acids, proteins are highlighted. Mechanical and electrical properties of FET devices and their effect on performance is discussed. This review provides a guiding role in the design and development of FET-based biosensors.